Illocutionary speech acts in motivational TEDx Talks by young Indonesian speakers on YouTube - Nofiyanti; Fadilah, Eka; Linuwih, Endar Rachmawaty (Journal of English Language and Pedagogy (JELPA), 2025)
This research analyzes illocutionary speech acts in selected TEDx Talks delivered by Zhafira Aqyla and Fathia Fairuza on YouTube. It focuses on two main objectives: identifying the types of illocutionary acts and examining their communicative functions. Using Searle’s 1976 classification—representative, directive, commissive, expressive, and declarative—this qualitative study applies documentation and note-taking techniques for data collection. Findings show that a total of 158 utterances were identified: 78 from Zhafira’s talk and 80 from Fathia’s. Representative acts were the most dominant (115 occurrences), followed by directive (30), commissive (8), and expressive (5) acts; declarative acts were not found. The most frequently observed functions include stating (42), describing (29), informing (18), advising (11), and reporting (18). These functions reflect how each speaker conveyed intentions such as informing, persuading, encouraging, or engaging the audience. The results show the significance of illocutionary functions in shaping speaker intention and audience impact, particularly on digital public speaking platforms like TEDx Talks.